EROSIVE EFFECT OF ACIDIC BEVERAGES ON THE SURFACE OF FILLING MATERIALS - P Holík; Y Morozova; M Rosa; I Voborná (Czech Dental Chamber, 2022)
Introduction, aim: Erosive-abrasive defects of hard dental tissues are, in addition to tooth decay, one of the most common dental pathologies. Dental filling materials designed to repair these defects must be able to withstand the effects of wear - that is, erosion and abrasion - comparable or better than the enamel they replace. The study is focused on determining the surface changes of filling materials of various categories after exposure to acidic pH. The aim is to verify that the filling materials resist acids better than tooth enamel. Methods: The immersion of the samples took place in Coca-Cola (pH 2.4) for 5 minutes and for the sake of the erosive process also for 14 days. Image analysis using a confocal laser scanning microscope was used to examine the samples. Changes in surface hardness were also evaluated by nanoindentation and compared with enamel. Results: The tested filling materials, contrary to the enamel, withstood short-term exposure without significant changes in hardness and appearance. However, micro and macroscopic changes were observed during long-term exposure. These changes were most evident in the group of glass ionomer filling materials. Conclusion: The observations clearly showed a significantly higher resistance of the filling materials to the acidic environment than that of the enamel.